The Relationship between Nutritional Status and Lifestyle with Risk of Early Menarche among Adolescent - Iqlima Dwi Kurnia (Journal of Global Pharma Technology, 2016)
Introduction: Early menarche is one of the major of concern in reproductive health, and affects a large number of women throughout their reproductive life from early adolescent. Early menarche is an important indicator of sexual and reproductive health. The aim of this research was to explain the relation between nutritional status and lifestyle with early menarche case in-adolescent in Surabaya. Method: The research design used was cross sectional. The study population consisted of 232 early-adolescent. The study sample totaled 145 early adolescents based on Purposive sampling with a study period of 2 months. The independent variables were nutritional status and lifestyle, while the dependent variable was early menarch. The data collection method used was a questionnaire sheet filled out by the adolescents and BMI measurement. The statistical analysis used Spearman rho (α ≤ 0, 05). Results: The results showed that nutritional status and lifestyle were positively related to early menarche in early-adolescents (p = 0.000). Discussion: Overweight nutritional status or high BMI and unhealthy lifestyle will tend to experience early menarche. Early menarche can lead to a premature menapouse as well, the risk of heart and bone disorders.Keywords: Nutritional status, Lifestyle, Early menarche, Early-adolescent.